Mild and efficient copper-catalyzed oxidative cyclization of oximes with 2-aminobenzyl alcohols at room temperature: synthesis of polysubstituted quinolines. Issue 3 (5th January 2021) - Liu, Yan-Yun; Wei, Yang; Huang, Zhi-Hui; Liu, Yilin
Abstract : A simple and efficient protocol for the synthesis of polysubstituted quinolines at room temperature has been developed by ligand-free Cu-catalyzed oxidative cyclization of oxime acetates with 2-aminobenzyl alcohols. Abstract : A simple and efficient ligand-free Cu-catalyzed protocol for the synthesis of polysubstituted quinolines via oxidative cyclization of oxime acetates with 2-aminobenzyl alcohols at room temperature has been developed. The presented approach provides a new synthetic pathway leading to polysubstituted quinolines with good functional group tolerance under mild conditions. Moreover, this transformation can be applied for the preparation of quinolines on a gram scale. Oxime acetates serve as the internal oxidants in the reactions, thus making this method very attractive.